Strategic positioning of the organization in its environment (the flexibility approach) - Ogu, Sokari Jusih (YAYASAN MITRA PERSADA NUSANTARA, 2025)
This study explores the evolving dynamics of resource management, focusing on the relationship between human capital and product value creation. It examines how strategic positioning and resource engineering can enhance efficiency and innovation by treating employees as owners of their human capital. A qualitative approach, including thematic analysis of literature and case studies, was used to evaluate organizational models prioritizing personnel-product synergy, resource allocation, and their impact on value generation. Key metrics analysed included employee engagement, productivity, and product enhancement. The findings reveal a shift from a transactional to a continuum model of resource management, where employees, as dynamic human capital contributors, drive product value beyond intrinsic levels. Strategic positioning plays a crucial role, involving the reallocation of resources to functional variables. This dynamic process, termed